Prevalence of oral diseases in children of 6, 12 and 15 years-old in Islay (Arequipa, Peru) - Villagra Valdivia, Thais (2020)
Objective: To determine the prevalence of oral diseases in children 6, 12 and 15 years old in Islay, Arequipa. Materials and methods: Observational, descriptive and cross-sectional study. The sample consisted of 360 students of 6, 12 and 15 years of age of both sexes who met the inclusion criteria. The level of confidence was determined at 95% and the margin of error at 5%. To evaluate oral pathologies, the OHI-S, OHI-M, mPI/PI, DMFT, DMFS, the WHO and the Dean index were used. The students were examined visually and clinically. Results: Regarding IHO-S: good hygiene was observed in 72.5% in deciduous and 63.3% in permanent teeth; regular hygiene was found in 27.5% in deciduous and 35.0% in permanent teeth with poor hygiene in 1.7% in permanent teeth and significant differences in age. The CPOD showed 6.71 carious, 0.14 lost, 1.44 blocked and an average of 8.29 with significant differences in relation toage. According to the IPC-M, 81.4% had gingivitis, 57.5% periodontitis, 4.2% severe periodontitis, with significant differences for age. Malocclusions included: normal occlusion 38.9%, mild malocclusion 38.6% and moderate or severe 22.5%; 61.1% had malocclusions. In relation to fluorosis, 34.7% had no lesion, 15%questionable fluorosis, 30.3%very mild fluorosis, 11.7% mild fluorosis, and 1.1% moderate fluorosis with a prevalence of 58.1%. Conclusions: The prevalence of oral diseases and the risk of dental caries are high in children, with regular and poor hygiene being observed in permanent dentition. The percentage of gingivitis is high. The prevalence of malocclusions ranges from mild to moderate while the prevalence of dental fluorosisis is low.